KARL MARX DAN FRIEDERICH NIETZSCHE TENTANG AGAMA - Ahmad Muttaqin (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2013)
Karl Marx and Friedrich Nietzsche are two figures that are considered controversial inreligious studies. Both stated that â€˜religion is the opium and the God is deadâ€™ are deemed to havepassed the limits of tolerance. As a result, both are regarded as insane person in their time.When they are examined more deeply, both statements expressed deep concern over thesocial situation of the people that suffer as a result of oppression and domination. In thissituation, religion precisely be one that encourages people to behave naive and counterproductiveto the objectives of humanitarian material. Thus, â€œreligion is the opium and God is deadâ€ aresocial provocation and criticism for people to get out of the traps of stagnation.The purpose of human life is material. For Marx, human nature is working, while forNietzsche, it is the willing to power. This means that human will be humanic if it human is ableto express in productive work that is free from domination and have the will to implement thepowers that are pushing for continually active and creative. Initially, religion supports human tomanifest true humanity but evolved into rituals that hinder the process of humanization.